Diabetes Self-Care Management (DSCM) experience individuals with type 2 diabetes mellitus - Anih Kurnia; Farida Mohd Said; Santhana Letcmi Paduragan; Suci Rahma Pratiwi; Meri D; Eli Kurniasih (Riset Informasi Kesehatan, 2023)
Background : Self-Care Management is an important part of the lives of individuals with chronic diseases. This is important because they have to adapt their conditions so that they are able to make decisions about how to manage their own health condition. (Objective) This study aims to gain an in-depth understanding of the meaning of diabetes self-care management (DSCM) in type 2 diabetic individuals . Method: This study uses a qualitative method with a descriptive phenomenological approach. The sampling technique used was purposive sampling. Data saturation occurred in the 4th participant so the participants involved in this study were 4 people with inclusion criteria consisting of 1) Diabetes Mellitus Type 2 (DMT2) individuals with a period of â‰¥ 6 months; 2) those who did not experience severe complications (such as severe stroke, heart disease, and diabetic ketoacidosis; 3) was able to tell his experience. Data were taken through in-depth interviews for approximately 60 minutes. Data analysis using Colaizziâ€™s method. Results: The results of the study identified nine themes, including 1) physical responses experienced by people with Diabetes Mellitus Type 2 (T2DM); 2) perception; 3) Self-awareness; 4) routine blood sugar control; 5) adherence to diet; 6) physical activity; 7) adhere to treatment; 8) self-efficacy; 9) non-pharmacological therapy lowers blood sugar levels. Conclusion: DSCM is important in the management of Diabetes Mellitus Type 2 (DMT2). A better DSCM can reduce complications, reduce visits to health services, and treatment costs and reduce morbidity and mortality. Further research is needed to explore the content stored in DSCM. Key words: Diabetes self-care management, Diabetes mellitus Type 2 (DMT2), qualitative